(untitled) - Mueller, John Paul (New Jersey, 2005)
For large-scale web application development, Visual Studio 2005 is the most capable product around. This book shows team members and leaders how to use its power in several key dimensions. You'll master dozens of built-in features for creating a large, high-performance website based on ASP.NET 2.0. You'll work seamlessly with dynamic data, both reading from and writing to databases. And throughout, you'll learn how Visual Studio 2005 supports a more efficient group process in terms of design, development, and deployment. And everything is brought together with the enterprise-scale example, "ABC Incorporated," that runs throughout the book. This is a book no web developer, and no web-dependent organization, should be without.
Keywords: Web site development,Application software; Computer programs,Development; Computer programs